Wind-induced responses of a tall chimney by aeroelastic wind tunnel test using a continuous model. (1st December 2018) - Liang, Shuguo; Yang, Wei; Song, Jie; Wang, Lei; Hu, Gang
Highlights: A continuous aeroelastic chimney model was manufactured with the DEVCON plastic steel liquid. The roughness paper strips were attached to the model surface to artificially achieve effective high Reynolds number flow. An optimal thickness of the roughness paper strips was determined. The response of the roughened model is much smaller than that for the model without roughness element. The across-wind acceleration response is usually larger in the more turbulent wind flow. Abstract: This study aims to investigate wind-induced responses of a 300 m high chimney by using wind tunnel tests on an aeroelastic model. Due to the fact that it is unrealistic to simulate wind flow with a high Reynolds number as high as 1 × 10 8 for a chimney model in a wind tunnel, roughness paper strips were attached to the model surface to artificially achieve effective high Reynolds number flow in the full-scale condition. An optimal thickness of the roughness paper strips was determined via a series of pressure measurement tests on a rigid model of the chimney. To examine wind-induced responses of the chimney, a continuous aeroelastic chimney model was manufactured with the DEVCON plastic steel liquid. After roughening the aeroelastic model by the paper strips with the optimal thickness, a series of wind tunnel tests were conducted on the model to directly acquire the structural responses, for three different oncoming wind flow conditions. Results show that the response of the roughened model is much smaller than that for the model without roughness element, indicating that ignoring the Reynolds number effect will overestimate the response. The across-wind acceleration response of the chimney is more considerable than that in the along-wind direction, when the reduced wind velocity Vr is larger than 4. In addition, the across-wind acceleration response is usually larger in the more turbulent wind flow, although the lock-in phenomenon is more evident in uniform flow.